Techniques of international trade : Revision of Technical procedure in exporting and importing - Rosenthal, Morris Sigmund (New York : McGraw-Hill, 1950)
This book describe in full details each of the techniques that an international trader should be conversant with.
includes appendixes
includes index
ijb, 17/01/2019
Loans
Keywords: international trade - Techniques; Commerce